Critical analysis and assessment of EU policy on multifunctional land use activities in rural areas - Diana Kopeva; Mariya Peneva; Omar Baquiero; Ramona Franić; Guy Garrod; Baptiste Hautdidier; Nedka Ivanova; Miroslav Jelinek; Marta Konecna; Ramon Laplana; Burghard Meyer; Mario Njavro; et al. (Regional and Business Studies, 2011)
Rural areas are becoming increasingly differentiated and gradually losing their agricultural specificity. They now need to support the coexistence of two logical approaches to occupation of their space: one based on the supply of agricultural and forestry products, the other on the various demands from local residents and seasonal tourists. Under these conditions the roles of agriculture, forestry, and tourism industry are evolving; the focus is no longer simply on supplying market goods while limiting the impacts of this supply on negative external factors but now also on participating in land development and meeting the manifold expectations of society. The paper analyses EU policies related to multifunctional land use activities on the national and regional level. The policy framework within which multifunctionality of land use activities is realized is determined by three EU policies, namely the Cohesion Policy, Rural Development Policy, and Enlargement Policy. The paper focus on six cases: Bulgaria, Czech Republic, Croatia, Germany, France and UK. Three of the case study sites (in Czech Republic, Bulgaria and Croatia) were/are influenced by the financial instruments of the Enlargement policies (PHARE, SAPARD, ISPA, IPA). The impact of EU policies is assessed in three domains – economic, social and environment. The scope of impact of the major driving forces for multifunctional land use activities is assessed and analyzed.
Keywords: 330; multifunctionality; EU policy; rural development